STRATEGI KESANTUNAN BERBAHASA DALAM ACARA STAND UP COMEDY di KOMPAS TV SEASON 4 - Dewin Meini; Hasnah Faizah; Dudung Burhanudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to investigate the politeness of language Strategy from Stand Up Comedy show season 4 by Kompas Tv. The purpose of this study was to describes positive politeness strategy and negative politeness strategy from Stand Up Comedy show season 4 by Kompas Tv. The kind of this study was used qualitative of descriptive method. This study aims to exploring, describing and explanation a variation, symptoms, or the systematically circumstances, factual and accurately about the data, the characteristics and phenomena. The sources of data was a video of Stand Up Comedy has theme “social critics” by comedian of Indonesia contained by Kompas Tv seasons 4 taken from youtube. Technique of collecting data of this was listening technique. Data analysis techniques were listening and watching the videos of stand up comedy, reading, determining data, grouping data, and performing data analysis. Based on the was found six of Stand Up Comedy videos season 4 by 27 speeches of comedians used 12 positive politeness strategies and 39 speeches of comedians comedian used 9 negative politeness strategy.Keywords: Politeness Of Language Strategy, Stand Up Comedy